'A poor and precious secret': cinema's remediation in Patrick Modiano's Dora Bruder. Issue 7 (3rd July 2021) - Kouvaros, George
ABSTRACT: 'Doesn't a breath of the air that pervaded earlier days caress us as well?' Walter Benjamin asks in 'On the Concept of History'. 'In the voices we hear, isn't there an echo of now silent ones? … If so, then there is a secret agreement between past generations and the present one'. What does it mean to be in secret agreement with people that came before? To recognise that coming after involves the taking on of certain obligations – for example, to pay tribute, to make amends. This paper examines the role played by the cinema in Patrick Modiano's Dora Bruder . Part history, part memoir, Modiano's book investigates the events leading to the deportation of a sixteen-year-old Jewish girl during the Nazi Occupation of France. The author's examination of these events commemorates the lives lost during the Occupation and alerts us to what remains still to be said about these lives. The issue that I address concerns cinema's role in the author's evocation of Dora's afterlife, in other words, its facilitation of a type of writing in which the experience of the present is shaped by the unfinished business of people and events that demand something of us.